Illocutionary Acts Analysis on Short Story Entitled Mr. Know All - Yaqin, Ainul (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2024)
In everyday conversation, while producing utterances people also perform actions via those utterances. This phenomenon not only occurs in real-life conversations but also can occur in a dialogue of a short story. The present study was conducted to analyze illocutionary acts in a short story dialogue entitled Mr. Know All written by Somerset Maugham. The type of this research was descriptive qualitative research. The data were the utterances produced by the characters in the story. The analysis of the data was based on the theory of illocutionary acts proposed by Searle (1979). The result indicated that the characters performed five types of illocutionary acts in the dialogues; they are assertive, directive, commissive, expressive, and declarations. The most frequent illocutionary acts performed in the dialogues were expressive.